Understanding the meaning of lactate threshold in resistance exercises - Garnacho-Castano, M. V.; Dominguez, R.; Mate-Munoz, J. L. (International Journal of Sports Medicine, 2015)
This study compares acute cardiorespiratory, metabolic, mechanical and rating of perceived effort (RPE) responses to 2 different prolonged constant-load exercises, half-squat (HS) and cycle ergometry, performed at a workload corresponding to the lactate threshold (LT). A total of 18 healthy subjects completed 5 exercise tests separated by 48?h rest periods: an incremental cycle ergometer test, a constant-load cycle ergometer test at LT intensity, a one-repetition maximum (1RM) HS test, an incremental HS test and a constant-load HS test at LT intensity. In both constant-load tests, cardiorespiratory, metabolic and RPE data were recorded. Mechanical responses before and after each test were assessed in terms of jump height and mean power measured in a counter movement jump (CMJ) test. In both exercises, cardiorespiratory and metabolic responses stabilized, though cardiorespiratory responses were significantly greater for cycle ergometry (P<0.001), with the exception of respiratory exchange ratio (RER), which was higher for HS (P=0.028). Mechanical fatigue was observed in only HS (P<0.001). In conclusion, different exercise modalities induced different yet stable acute cardiorespiratory and metabolic responses. Although such responses were significantly reduced in HS, greater mechanical fatigue was produced, most likely because of the particular muscle actions involved in this form of exercise.